(untitled) (Research, Society and Development, 2024)
Objective: To analyze the applications of low-level laser in the treatment of GEHA through a literature review. Methodology: This is a literature review study that sought to analyze the applications of low-level laser in the treatment of acute or primary herpetic gingivostomatitis. For the literature search, articles available in Google Scholar, BVS and Pubmed were selected. The controlled descriptors used and listed by the Health Sciences Descriptors (DeCS) were: "Laser", "Photodynamic" and "Herpetic". The descriptors were crossed using the AND or OR operator, constructing the following search key (("laser" or "Photodynamic") and "herpetic")). The data were organized by content analysis, highlighting the most relevant points that the literature addresses on the subject, in addition to discussing the results of the studies with the literature. Results and discussion: The use of laser when associated with the antiretroviral acyclovir presents great efficacy in the treatment of lesions. Conclusion: The use of low-power laser in ulcers caused by acute herpetic gingivostomatitis appears to be an excellent line of treatment for the disease, with the possibility of offering good results, and which would bring more benefits to patients if more professionals began to use it in conjunction with support measures, resulting in better well-being for patients and an optimization of the time to cease symptoms.